Repeated Low-Level Blast Overpressure Leads to Endovascular Disruption and Alterations in TDP-43 and Piezo2 in a Rat Model of Blast TBI - Heyburn, Lanier; Abutarboush, Rania; Goodrich, Samantha; Urioste, Rodrigo; Batuure, Andrew; Statz, Jonathan; Wilder, Donna; Ahlers, Stephen T.; Long, Joseph B.; Sajja, Venkata Siva Sai Sujith (Frontiers in Neurology, 2019)
Recent evidence linking repeated low-level blast overpressure exposure in operational and training environments with neurocognitive decline, neuroinflammation, and neurodegenerative processes has prompted concern over the cumulative deleterious effects of repeated blast exposure on the brains of service members. Repetitive exposure to low-level primary blast may cause symptoms (subclinical) similar to those seen in mild traumatic brain injury (TBI), with progressive vascular and cellular changes, which could contribute to neurodegeneration. At the cellular level, the mechanical force associated with blast exposure can cause cellular perturbations in the brain, leading to secondary injury. To examine the cumulative effects of repetitive blast on the brain, an advanced blast simulator (ABS) was used to closely mimic “free-field” blast. Rats were exposed to 1-4 daily blasts (one blast per day, separated by 24 hours) at 13, 16, or 19 psi peak incident pressures with a positive duration of 4-5 msec, either in a transverse or longitudinal orientation. Blood-brain barrier (BBB) markers (vascular endothelial growth factor (VEGF), occludin, and claudin-5), transactive response DNA binding protein (TDP-43), and the mechanosensitive channel Piezo2 were measured following blast exposure. Changes in expression of VEGF, occludin, and claudin-5 after repeated blast exposure indicate alterations in the BBB, which has been shown to be disrupted following TBI. TDP-43 is very tightly regulated in the brain and altered expression of TDP-43 is found in clinically-diagnosed TBI patients. TDP-43 levels were differentially affected by the number and magnitude of blast exposures, decreasing after 2 exposures, but increasing following a greater number of exposures at various intensities. Lastly, Piezo2 has been shown to be dysregulated following blast exposure and was here observed to increase after multiple blasts of moderate magnitude, indicating that blast may cause a change in sensitivity to mechanical stimuli in the brain and may contribute to cellular injury. These findings reveal that cumulative effects of repeated exposures to blast can lead to pathophysiological changes in the brain, demonstrating a possible link between blast injury and neurodegenerative disease, which is an important first step in understanding how to prevent these diseases in soldiers exposed to blast.